Unimodal and multimodal regions for logographic language processing in left ventral occipitotemporal cortex - Deng, Yuan; Wu, Qiuyan; Weng, Xuchu (Frontiers in Human Neuroscience, 2013)
The human neocortex appears to contain a dedicated visual word form area (VWFA) and an adjacent multimodal (visual/auditory) area. However, these conclusions are based on functional magnetic resonance imaging (fMRI) of alphabetic language processing, languages that have clear grapheme-to-phoneme correspondence (GPC) rules that make it difficult to disassociate visual-specific processing from form-to-sound mapping. In contrast, the Chinese language has no clear GPC rules. Therefore, the current study examined whether native Chinese readers also have the same VWFA and multimodal area. Two cross-modal tasks, phonological retrieval of visual words and orthographic retrieval of auditory words, were adopted. Different task requirements were also applied to explore how different levels of cognitive processing modulate activation of putative VWFA-like and multimodal-like regions. Results showed that the left occipitotemporal sulcus responded exclusively to visual inputs and an adjacent region, the left inferior temporal gyrus, showed comparable activation for both visual and auditory inputs. Surprisingly, processing levels did not significantly alter activation of these two regions. These findings indicated that there are both unimodal and multimodal word areas for non-alphabetic language reading, and that activity in these two word-specific regions are independent of task demands at the linguistic level.